APPLICATION OF QR-CODE-ASSISTED POSTER MEDIA TO IMPROVE DIGITAL LITERACY OF GRADE VIII STUDENTS OF SMP NEGERI 49 MAKASSAR - Thya Enjely Ningsi; Sitti Rahma Yunus; Ramlawati Ramlawati (Jurnal IPA Terpadu, 2024)
This study aims to find out: 1) The level of students’ digital literacy before and after the application of QR-Code Assisted Poster media. 2) Improvement of students’ digital literacy after the implementation of QR-Code Assisted Poster media. 3) Significant improvement in digital literacy after the implementation of QR-Code Assisted Poster media. This research is a Pre-Experimental research with One Group Pretest-Posttest Design. The research population is all students of grade VIII of SMP Negeri 49 Makassar which consists of 5 classes with a total of 126 students. Sample was selected by pusposive sampling, with 1 class, namely class VIII.1 which totals 21 students. The research instrument is a digital literacy questionnaire. It was concluded that: 1) The level of digital literacy of students before the implementation of QR-Code-assisted poster media was in the low category with an average score of 37.29, and after the implementation of QR-code-assisted poster media had an average score of 68.76 with a high category. 2) The average N-Gain of digital literacy of students after applying QR-Code-assisted poster media was 0.66 with the medium category. 3) There was a significant increase in students' digital literacy after the implementation of QR-Code-assisted poster media.